The Effect of Different Storage Temperatures over Time on the pH of Mammary Gland Secretions in Periparturient Mares - Canisso, Igor F.; Amorim, Gabrielle B. A. G. [UNESP]; Magalhaes, Humberto B. (MDPI, 2024)
The objectives of this study were (i) to determine pH and electrolyte concentrations in MGS collected prepartum and at parturition, (ii) to characterize mare milk pH during the first week postpartum, and (iii) to evaluate pre-foaling MGS pH at three storage temperatures. This study outlined two hypotheses: (i) all mares exhibit acidic pH, increased calcium, magnesium, and potassium, and reduced sodium concentrations regardless of prepartum pH and electrolytes; (ii) pre-foaling MGS pH varies with storage temperature and time in an initial value-dependent manner. Twenty-three multiparous mares were monitored daily from 320 days of gestation until parturition. Pre-foaling MGS was collected, and pH was immediately measured using a hand-held pH meter. Aliquots were preserved for further electrolyte analysis. Postpartum, samples from day −7 to 0 (day of foaling) were thawed, and electrolyte concentrations (calcium, magnesium, sodium, potassium) were determined. For the three storage temperatures, pH was measured at 0, 15, 30, 45, and 60 min after storage, and hourly for 10 h post-collection. A range of pH 8 to 6.5 was included to avoid bias towards a specific pH value. The chosen pH groups were 8 (range 7.8–8.2), 7.5 (range 7.3–7.7), 7 (6.7–7.2), and 6.5 (6.2–6.6). Overall, storage temperature affects pH (p < 0.05). In conclusion, this study demonstrated that the majority of the mares had sodium–potassium inversion and acidic pH at foaling. Milk pH is neutral up to four days after foaling, becoming slightly alkaline afterwards, with undetermined clinical significance. The pH of MGS showed minimal variation across storage temperatures, except for pH ~7.5, which increased to ~8 post-storage. This study is the first to address these physiological and practical questions about MGS pH in periparturient mares.
Keywords: equine; foaling; horse; impending parturition